(untitled) (Fisioterapia e Pesquisa, 2023)
The high prevalence of depressive symptomsin older adults highlights the importance of investigatingrisk factors that may contribute to this condition, especiallythose that are subject to effective interventions, such asthe neighborhood environment. However, the associationbetween perceived characteristics of the environment and presence of depressive symptoms in Brazilian older adults,as well as in those who attend Primary Health Care (PHC)units is not yet fully established. This study aimed to verify theassociation between the perception of the neighborhood andpresence of depressive symptoms in community-dwelling olderadults. This is a cross-sectional, household-based study with aprobabilistic sample. A total of 293 community-dwelling olderadults (57.3% women; 54.7% aged 60–69 years) and registeredin the municipal Primary Health Care System of BalneárioArroio do Silva/SC were included. Depressive symptoms wereassessed using the Geriatric Depression Scale (GDS) andthe perception of the environment was obtained using theadapted instrument Neighborhood Environment WalkabilityScale (NEWS). Associations were tested by multivariatelogistic regression. Significant negative associations wereobserved between the presence of food establishments(OR: 0.52; 95%CI: 0.28–0.98), health clinics and communitycenters (OR: 0.52; 95%CI: 0.28–0.96), outdoor gyms(OR: 0.38; 95%CI: 0.20–0.72), fitness centers and/or clubs(OR: 0.42; 95%CI: 0.19–0.89), well-maintained sidewalks(OR: 0.37; 95%CI: 0.19–0.71), pedestrian signals (OR: 0.39; 95%CI:0.18–0.84), and neighborhood safety for walking during theday (OR: 0.35; 95%CI: 0.16–0.76) and night (OR: 0.40; 95%CI:0.19–0.83) and the presence of depressive symptoms. It wasconcluded that there is inverse associations between betterperceived characteristics of the environment and the presenceof depressive symptoms in community-dwelling older adults,demonstrating the importance of promoting strategies toimprove the neighborhood infrastructure and prevent depressivesymptoms in this population